2022
DOI: 10.3390/foods11111635
|View full text |Cite
|
Sign up to set email alerts
|

Association of Seaweed Consumption with Metabolic Syndrome and Its Components: Findings from the Korean Genome and Epidemiology Study

Abstract: This study aimed to investigate the association between seaweed consumption and the odds of developing metabolic syndrome in middle-aged and elderly Koreans. The study included 5777 adults aged 40–69 years from 2001 to 2002 in the Ansan and Ansung cohorts of the Korean Genome and Epidemiology Study. Data on the consumption of seaweed, including laver and kelp/sea mustard, were obtained using a semiquantitative food frequency questionnaire. Multivariable logistic regression models were used to assess the associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 44 publications
2
4
0
Order By: Relevance
“…In men with the highest total seaweed, intake was significantly associated with a decreased incidence of MetS compared with that in men with the lowest seaweed intake. In line with previous findings, a cross-sectional study found that seaweed intake decreased MetS incidence in middle-aged men (OR 0.70, 95% CI 0.54-0.92) [26]. In a prospective cohort study of 2588 postmenopausal women, seaweed intake and dietary iodine decreased the incidence of MetS (HR 0.52, 95% CI 0.39-0.69; HR 0.61, 95% CI 0.47-0.78, respectively) [35].…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…In men with the highest total seaweed, intake was significantly associated with a decreased incidence of MetS compared with that in men with the lowest seaweed intake. In line with previous findings, a cross-sectional study found that seaweed intake decreased MetS incidence in middle-aged men (OR 0.70, 95% CI 0.54-0.92) [26]. In a prospective cohort study of 2588 postmenopausal women, seaweed intake and dietary iodine decreased the incidence of MetS (HR 0.52, 95% CI 0.39-0.69; HR 0.61, 95% CI 0.47-0.78, respectively) [35].…”
Section: Discussionsupporting
confidence: 90%
“…Seaweed intake has been reported to help prevent MetS in several studies [23][24][25][26][27][28][29]. In a 4-week placebo-controlled study, seaweed fucoxanthin supplementation (1 mg/day) decreased waist circumference (WC) and fat mass in obese Japanese individuals aged 20-59 years [23].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations